Cinnamaldehyde Downregulation of Sept9 Inhibits Glioma Progression through Suppressing Hif-1α via the Pi3k/Akt Signaling Pathway. (19th January 2022) - Wang, Zhiwen; Wang, Changfeng; Fu, Jieping; Liu, Ruen; Zhou, Xinhui
Abstract : Purpose . Cinnamaldehyde (CA) is the main ingredient in cinnamon, and it has been proven to have an inhibitory effect on many different tumor types. However, it lacks effect on glioma. This paper explores the effect CA has on glioma cells U87 and U251 at the cellular and molecular levels. Methods . The relationship between Hif-1 α and Sept9 was found by CGGA. Cell Viability Assay (CCK8) was made to detect the proliferation ability. The scratch experiment and the transwell experiment were applied to the migration and invasion ability. Annexin V-FITC/PI were used to detect the cell apoptosis. Western blotting was used to determine the specified protein level. Results . Cell proliferation assay results revealed CA to inhibit the proliferation of glioma cells in a dose-dependent manner. It promoted apoptosis for upregulating the expression of Bax and downregulating the expression of Bcl-2. Wound Healing Assay and transwell test found CA to have anti-invasion ability and that it upregulated the expression of E-cadherin and downregulated the expressions of MMP-2 and MMP-9. The molecular mechanism was studied from a tumor microenvironment (TME) perspective. Pi3k inhibitor (LY294002) was used for interfering with cells, and the results found CA to demonstrate a similar effect. Hif-1 α and Sept9 expressions were inhibited, and Akt and p-Akt were also inhibited. By using CoCl2 to make hypoxia, CA was discovered to inhibit the high expression of Hif-1 α and Sept9, demonstrating a correlation with the Pi3k/Akt pathway. It is suggested that the mechanism of Sept9 under hypoxia regulation can be realized through the Pi3k/Akt pathway. Conclusions . This study proves for the first time that CA is an effective drug for inhibiting the proliferation of glioma through Sept9 and reveals Sept9 to be related to the Pi3k/Akt pathway in terms of tumor microenvironment, providing a molecular basis for the further study of CA in glioma treatment.